Development of three-dimensional facial approximation system using head CT scans of Japanese living individuals. (June 2019) - Imaizumi, Kazuhiko; Taniguchi, Kei; Ogawa, Yoshinori; Matsuzaki, Kazutoshi; Maekawa, Hidemasa; Nagata, Takeshi; Moriyama, Tsuyoshi; Okuda, Itsuko; Hayakawa, Hideyuki; Shiotani, Seiji
Highlights: A software for 3D facial approximation from the skull based on CT scans of Japanese individuals was developed. The analyses were made by creating anatomically homologous shape models. The approximate head shapes of known individuals showed a relatively good resemblance. Approximation errors were identified, particularly in areas with thick surficial tissue. Referential models for the craniofacial superimposition were made. Abstract: We developed software for three-dimensional (3D) facial approximation from the skull based on computed tomography (CT) scans of the head obtained from 59 Japanese adult volunteers (40 males, 19 females). CT scanning was performed while participants raised their head in an upright position while in a prone body posture. The positional relationships between the skull and head surface shape were analyzed by creating anatomically homologous shape models. Before modeling, skull shapes were simplified by concealing hollow structures of the skull using in-house software. Surficial tissue thickness (STT), represented by the distances between corresponding vertices of the simplified skull and head surface, was calculated for each individual, and averaged for each sex. Although the approximate head shapes of known individuals showed a relatively good resemblance in both the shape of the whole head and facial parts, some errors were identified, particularly in areas with thick surficial tissue. The results revealed sexual dimorphism of STT, with males exhibiting thinner surficial tissue at the cheek, and thicker tissue at the glabella, nose, mouth, and chin. Moreover, we created referential models for craniofacial superimposition from average models of the skull and head surface shape for each sex.